Antibacterial efficacy of Clidemia hirta leaf extract against pathogenic fish bacteria - Setiaji Jarod; Febrian Prakoso Valentio; Heriyanto; Melati Hisra; Azhari Handika; Nur Ramadhan Anugrah; Muhammad Samin Saproni (BIO Web of Conferences)
Bacterial diseases pose a serious threat to aquatic ecosystems, and the use of antibiotics to address these problems can have harmful effects on both fish and their environment. Therefore, there is an increasing demand for safe natural alternatives to treat fish diseases. This research investigates the antibacterial properties of an extract from Clidemia hirta against various bacterial strains, including A. salmonicida, P. aeruginosa, E. ictaluri, A. hydrophila, V. alginolyticus, and E. tarda. Phytochemical analysis of the extract identified the presence of phenolic compounds, terpenoids, saponins, and flavonoids. The antibacterial effectiveness of the C. hirta extract was assessed using the agar diffusion method at concentrations of 50, 100, 150, 200, and 250 mg/mL. The findings indicated that the extract significantly inhibited the growth of A. salmonicida (16.5 mm to 23.3 mm), P. aeruginosa (17.3 mm to 23.5 mm), E. ictaluri (15.3 mm to 23.5 mm), A. hydrophila (15.3 mm to 21.8 mm), V. alginolyticus (16.8 mm to 22.8 mm), and E. tarda (15.0 mm to 22.8 mm). In summary, the extract from C. hirta shows potential as a natural agent to control pathogenic bacteria affecting fish.